2020
DOI: 10.1186/s12888-020-02990-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to monitoring and management of cardiovascular and metabolic health of patients prescribed antipsychotic drugs: a systematic review

Abstract: Background The use of atypical antipsychotics which currently form the primary choice pharmacotherapy for several mental health conditions have been linked to cardiovascular and metabolic side effects. This systematic review aimed to investigate the barriers to monitoring and management of cardiovascular co-morbidities in patients prescribed antipsychotic medicines. Methods A protocol-led (CRD-42018106002) systematic literature review was conducted by searching Medline, Embase, and PsycINFO databases 2003 unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…However, important gaps in the routine screening of metabolic disorders are found in clinical practice [ 82 ]. The barriers associated with these gaps include healthcare system-related factors such as the fragmentation of care and time and resources constraints, and patient-related factors such as disability resulting from mental health conditions, knowledge, and skills of the patients [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, important gaps in the routine screening of metabolic disorders are found in clinical practice [ 82 ]. The barriers associated with these gaps include healthcare system-related factors such as the fragmentation of care and time and resources constraints, and patient-related factors such as disability resulting from mental health conditions, knowledge, and skills of the patients [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46] Clinical guidelines should be inclusive of social outcomes such as homelessness when providing services for substance misuse and severe mental illnesses. [47][48]…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…A systematic review identified several multidimensional barriers to adequate monitoring for patients on antipsychotic medication. 56 Considering the variation between practices, it has previously been suggested that there are marked variations in mental health prescribing between general practices in the UK. [57][58][59][60] However, the variation in the prevalence of PSIs has only been examined in the UK using general (non-mental health specific) sets of PSIs.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%